Development of White Cabbage, Coffee, and Red Onion Extracts as Natural Phosphodiesterase-4B (PDE4B) Inhibitors for Cognitive Dysfunction: In Vitro and In Silico Studies - Nazir Ahmad; Kaisun Nesa Lesa; Navista Sri Octa Ujiantari; Ari Sudarmanto; Nanang Fakhrudin; Zullies Ikawati (Hindawi Limited, 2024)
Human cognition fundamentally depends on memory. Alzheimer's disease exhibits a strong correlation with a decline in this factor. Phosphodiesterase-4 B (PDE4B) plays a crucial role in neurodegenerative disorders, and its inhibition is one of the promising approaches for memory enhancement. This study aimed to identify secondary metabolites in white cabbage, coffee, and red onion extracts and identify their molecular interaction with PDE4B by in silico and in vitro experiments. Crushed white cabbage and red onion were macerated separately with ethanol to yield respective extracts, and ground coffee was boiled with water to produce aqueous extract. Thin layer chromatography (TLC)-densitometry was used to examine the phytochemicals present in white cabbage, coffee, and red onion extracts. Molecular docking studies were performed to know the interaction of test compounds with PDE4B. TLC-densitometry analysis showed that chlorogenic acid and quercetin were detected as major compounds in coffee and red onion extracts, respectively. In silico studies revealed that alpha-tocopherol (binding free energy (∆Gbind) = −38.00 kcal/mol) has the strongest interaction with PDE4B whereas chlorogenic acid (∆Gbind = −21.50 kcal/mol) and quercetin (∆Gbind = −17.25 kcal/mol) exhibited moderate interaction. In vitro assay showed that the combination extracts (cabbage, coffee, and red onion) had a stronger activity (half-maximal inhibitory concentration (IC50) = 0.12 ± 0.03 µM) than combination standards (sinigrin, chlorogenic acid, and quercetin) (IC50 = 0.17 ± 0.03 µM) and rolipram (IC50 = 0.15 ± 0.008 µM). Thus, the combination extracts are a promising cognitive enhancer by blocking PDE4B activity.